EDUCATIONAL COWORKING AS A NEW ORGANIZATION FORMAT OF EDUCATIONAL SPACE OF SUPPLEMENTARY VOCATIONAL EDUCATION - Galina A. Ignatyeva; Oksana V. Tulupova; Andrey S. Molkov (Russian State Vocational Pedagogical University, 2016)
The aim of the article is to reveal the essence of the educational coworking as a fundamentally new form of organization of teacher's innovative activity and relevant meaningful-activity technology of its exploration and practical implementation in the conditions of additional professional education (АPE). Methods. From the standpoint of anthropological project-transforming paradigm and reflective-positional approach the mission, content, structure and shape of the АPE, focused on the project-network and scientific-service support of innovative development of educational institutions and the formation of a new professional position of the teacher are disclosed. Based on the comparative analysis of mechanisms of coworking in economics, sociology and business education key characteristics of a model of educational co-working space are highlighted. The method of conceptual modeling of educational polypositional space of co-organization of the АPE subjects is applied. Results. The methodological framework of educational coworking is proposed and described including the problem area, realized in the project - analytical sessions; information area, based on today's knowledge-management technologies; the project - constructor area, where the project - network nodes format is implemented to work with al-ready initiated projects and the launch of new projects; organizational area where the cultivation is carried out a viable community of implementers of innovative projects; and the main unit - media-hub - concentration and distribution center in terms of growth time, personal resources, to ensure the movement of students on individual trajectories. Scientific novelty. Essential characteristics of the educational coworking, based on its understanding as a new organizational format that integrates professional training of the teacher in accordance with the social order and its professional development in terms of individual needs and capabilities are revealed. Practical significance. The educational model of coworking has a high potential in terms of growing new functional teaching positions in APE, transformation of pedagogical activity as a whole through the embedding of the activity standards in the practice of education.